(untitled) (Research, Society and Development, 2021)
Hepatitis B (HB) is responsible for several conditions such as cirrhosis and hepatocellular carcinoma. Prevention through vaccination is essential for people living with HIV, since this group has a higher rate of progression to the chronicity of the disease. The objective of the study was to analyze vaccination coverage against HB virus in the state of Piauí, through an epidemiological serum study of seropositive patients registered in the Laboratory Examination Control System (SISCEL) of the Central Laboratory of Public Health of Piauí in the year 2010. Data from 569 HIV-positive people were analyzed, with epidemiological variables such as age, color, education and serological markers for hepatitis B. The viral marker for hepatitis B, anti-HBs, was also determined. The findings were filtered and organized to compare the frequencies of anti-HBs titers among HIV-positive individuals. Seroconversion values ​​for anti-HBs were observed in only 39.7% of the participants, which confirms that lower rates of production of these antibodies occur in patients immunocompromised by HIV. According to the anti-HBs titles, key vulnerability behaviors were observed that make patients susceptible to infection, with emphasis on: family income and education, which point to the need to implement public policies that serve the population less favored.